Analysis of corticosteroids in urine by hplc and thermospray lc/ms - Park, S.-J.; Kim, Y.-J.; Pyo, H.-S.; Park, J. (1990)
The method for simultaneous determination and confirmation of nine corticosteroids in urine by high-performance liquid chromatography with a diode array detector and thermospray liquid chromatography-mass spectrometry was studied. HPLC was performed on a C18 column with a gradient mobile phase system of water and acetonitrile. The calibration curve was linear from 20 ng/mL to 1.0 μg/mL for each corticosteroid, and the detection limit was 10 ng/mL in 5 mL of urine. The extraction recovery of each corticosteroid from the spiked urine was equal to or greater than 85% by liquid-liquid extraction (LLE) at pH 9 using diethyl ether and approximately 79% or more by solid-phass extraction (SPE) with a Sep-Pak C18 cartridge. The mass spectra obtained with the positive ion mode showed protonated molecular species [M + H] +, ammonium adduct ion [M + NH4] +, [MH60]+, [MH30]+, and [MH18]+, The LC/MS detection limits ranged from 10 to 50 ng in the scan mode and from 1 to 5 ng in the selected ion monitoring (SIM) mode. ？ 1990 Oxford University Press.
Keywords: 11alpha hydroxyprogesterone; corticosteroid; corticosterone; cortisone; deoxycorticosterone; doping control; hydrocortisone; prednisolone; prednisone; triamcinolone; triamcinolone acetonide; unclassified drug; article; doping; drug analysis; high performance liquid chromatography; human; liquid chromatography; mass spectrometry; methodology; priority journal; urine; Adrenal Cortex Hormones; Chromatography, High Pressure Liquid; Chromatography, Liquid; Doping in Sports; Glucocorticoids, Synthetic; Human; Hydroxyprogesterones; Spectrum Analysis, Mass; Substance Abuse Detection